« Chercheur en résidence » : partager le quotidien professionnel de la conservation de la nature - Gaëlle Ronsin (Revue de Géographie Alpine)
The “Researcher-in-residence” experiment was born in 2015 in the Écrins National Park with the aim of enriching collaborations between the world of research, in environmental sciences, and the world of nature conservation. This incentive is based on the observation, shared by various authors and actors, that the links between these two professional worlds are too distant. Creating mechanisms for getting to know each other in a transdisciplinary manner would thus improve the ways of working and responding to the pressing issues of biodiversity conservation. This article firstly traces the genesis and concretization of this experiment through the singular trajectories of its first protagonists, which inform us about the relational, institutional and professional investments made in order to “get to know each other.” Secondly, the story of this experience illustrates that transdisciplinary collaboration involves moments of cross-professional learning. The interest of a residency, even a one-time one, thus lies in the sharing of temporalities and everyday knowledge in order to get to know each other in an epistemic and professional way.